LEXICAL CHANGE CAUSES OF JAVANESE LANGUAGE IN DELI SERDANG REGENCY. - Sutikno, wariyati, (LP2M Universitas Muslim Nusantara Al Washliyah, 2018)
This qualitative research addresses the lexical change in Javanese language, which is aimed at  explaining the lexical change reasons of Javanese language in Deli Serdang Regency. The transmigration process as the main aspects of creating Javanese language changes into variety accent and invite more action for the revitalization of language. The empirical materials were thoroughly and well-gathered from the document and interview. The highly critical and systematic analysis with âMiles and Huberman Modelâ reveals that Javanese language in Deli Serdang Regency changes. This research has drawn the following reasons of lexical changes of Javanese language in Deli Serdang Regency were linguistic causes, historical, environmental causes and psychological causes. The internal reasons are homonym (words which have the same phonemic structure but different meanings), phonetic attrition (the variations of meanings due to the sound change), and shortening. On the other hand, external factors are historical or social. Nevertheless, the social factor of lexical change pointed out is about cultural factor due to the wide definition of social factor itself, which might be cultural, historical, economic,ect. In addition, the reasons of language changes for language split and language borrowing are recognizable on this phenomenon since the Javanese language of Deli Serdang Regency has diversity in classifying of dialect.